إدارة التدريب عن بعد باستخدام الإنترنت لتنمية الموارد البشرية دراسة تطبيقية على جامعة سبها الليبية - Nasir Massoud Hassan
The study aims to link the management of distance training and the factors that affect the development of human resources and then develops a strategy to manage the proposed regulatory distance training for human resources development at the University of Sabha, Libya. The researcher used the descriptive analytical method and were adopted as a tool questionnaire and it was distributed to a sample of 235 respondent from university staff to get to know their point of view about the importance of managing distance training using the Internet for human resource development. The study concluded that there is potential for the integration of goals of the university and the existence of a clear strategy for training, especially working on optimal investment of human resources. The study recommended based on the result and the theoretical analysis and visualization of a proposal presented by the development of comprehensive plans to identify training needs for human resources at the University of Sabha in all disciplines, and develop training plans needed to meet these needs through distance training using the Internet.